Roles de género y salud en mujeres desplazadas por la violencia en Medellín, 2013-2014. - Posada Zapata, Isabel Cristina; Mendoza Ríos, Abraham; Orozco Giraldo, Isabel Cristina; Restrepo Correa, Carolina; Cano Bedoya, Sara María (Revista Ciencias de la Salud, 2017)
The phenomenon of displacement affects the entire Colombian population, especially the one that is most vulnerable, such as women, who see their health affected by the change of roles they must assume. Objective: To analyze how the roles of women displaced by violence influence their conditions of psychological and social vulnerability. Materials and methods: A qualitative research was carried out using the grounded theory method. There were primary sources, were the discourses collected via interviews with women who have been displaced by violence and who lived in one of three settlements in Medellin and whose characteristics were defined by cultural, ethnic and idiosyncrasic diversity, and secondary sources, that were obtained by reviewing official documents, literature, other studies and additional material on this issue. Data were collected through 15 semistructured interviews, six focus groups and six in-depth interviews. Coding, categorization and interpretation were used for the results analysis. Results: Displaced women are subjected to significant changes in their roles after the arrival in the city, including the scope of work, family and community, which influences their perception of health. The relationship between the multiple roles and their effect on women's vulnerability conditions cannot be studied by analyzing each role independently and without considering different functioning and adaptation dimensions of women. Conclusion: The experience of displacement by violence affects all the roles of the women in this situation, which in turn affects their vulnerability conditions and their perception of health.